Dust generation characteristics of hardwoods during the sanding process. - Ratnasingam, Jegatheswaran; Scholz, F.; Natthondan, V.; Garham, M. (Springer Berlin / Heidelberg, 2011)
A study of the factors that influence dust-generation during the sanding process of Malaysian hardwoods was undertaken. It was found that the amount of wood removed during the sanding process predetermined dust-generation, although the wood density and abrasive grit used also played a role. Consequently, low density wood species produced higher dust-concentration due to its relative ease of sanding, and vice-versa. The results of the study suggest that minimizing dust-generation during the hardwood sanding process could be achieved by ensuring minimal amount of wood removal as well as the use of the coarsest possible abrasive grit in the process.